VD_FINDINFO Jug / 2020 / 379 vom 11. März 2020 - VD Tribunal cantonal (2020)
CALOMNIE, PRÉSOMPTION D'INNOCENCE, INDIVISIBILITÉ, PLAINTE PÉNALE, APPRÉCIATION DES PREUVES | 174 ch. 1 CP, 32 CP, 33 CP, 10 CPP (CH)